Housekeeping gene as a source of calibrator candidate for HER-2 scoring in frozen tissue breast cancer study based on qPCR - RISMAYA RISMAYA; AZAMRIS AZAMRIS; SRI BUDIARTI; DESRIANI DESRIANI (Biodiversitas Journal of Biological Diversity, 2017)
Rismaya, Azamris, Budiarti S, Desriani. 2017. Housekeeping gene as a source of calibrator candidate for HER-2 scoring in frozen tissue breast cancer study based on qPCR. Biodiversitas 18: 1041-1046. HER-2 amplification in breast cancer gives an implication in therapy and prognosis. FDA have been approved Fluorescence In situ hybridization (FISH) for HER-2 amplification and immunohistochemistry (IHC) for protein expression measurement. In this recently times, quantitative PCR techniques have been reported as an alternative method for HER-2 amplification determination. Here in this report, we investigated new reference gene coming from housekeeping gene as an alternative calibrator for HER-2 amplification scoring based on qPCR methods. We compared two recommended housekeeping gene, 18S rRNA and ?-Actin, as a candidate for a HER-2 calibrator. For methods development, optimization and comparison study between 18S rRNA and ?-Actin, we used non-invasive samples (DNA buccal cells). Selected candidate reference further was tested to eighteen breast cancer sample, validated with qPCR methods refer to Mendoza et al. 2013. ?- Actin is shown as the best candidate for HER-2 scoring status determination. qPCR concordance result with other qPCR methods refers to Mendoza et al. 2013 shown 94.4%. The qPCR efficiency and % CV value shown as a requirement as a theory. qPCR efficiency was 103.8-105.3% for ?-Actin and HER-2 respectively while CV value was around 1.2%. Our result showed a significant correlation with reported methods, which could potentially complement with FDA approved methods.